ARTIFICIAL INTELLIGENCE FOR CYBERSECURITY: A SYSTEMATIC MAPPING OF LITERATURE - Ishaq Azhar Mohammed (International Journal of Innovations in Engineering Research and Technology, 2020)
This paper discussed how artificial intelligence (AI) may be used to address cybersecurity issues. Although secure communication between people, services, and devices is possible via centralized digital organizations, there are significant dangers associated with the digital revolution. Data mining, profiling, and exploitation are can be done without the users' expressed permission [1]. The continued provision of central solutions from service providers is wasteful in duplication, has significant security deficiencies, and is difficult for users. Digital identity authentication and verification are critical for ensuring the privacy and security of dispersed digital identities. However, the present body of knowledge is deficient in terms of thorough studies on unified communications aspects as well as user privacy and data security measures included in identity management systems. Digital identity management and verification are almost certainly the most promising of the many emerging applications of blockchain technology. In 2018, individual security breaches affected billions of individuals worldwide. Unquestionably, more secure methods of storing, exchanging, and validating sensitive data are required. In this respect, the development of blockchain solutions for identification systems may offer helpful solutions to some of the issues that most centralized databases face. Physical devices and human impedance are inadequate to manage and protect against cybercrime. Criminals utilize the Internet to perpetrate a wide variety of cybercrimes [1]. The experts seek assistance in preventing assaults and security breaches, as well as responding to attacks. The primary objective of cybersecurity is to minimize assaults via the use of AI technologies. There are existing applications of artificial intelligence in cybersecurity, and certain cybersecurity problems may be addressed via the use of AI methods, as well as some beneficial AI applications [2].